2017
DOI: 10.1080/00207543.2017.1308032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis for justification of utilising special purpose machine tools in the presence of uncertain parameters

Abstract: Decision-makers in manufacturing area frequently face machine tool selection problem under uncertainty due to competitive market changes. Special purpose machines (SPMs), a relatively new class of reconfigurable machine tools, are used to react quickly to changes. Justification of utilising these machines vs. other machine tools requires a technique to investigate the sources of uncertainties. In this work, sensitivity analysis is utilised to investigate the sources of these uncertainties and errors which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The analysis demonstrated that the unit production cost is inversely proportional to profit while the selling price per unit is directly proportional to profit. The results are consistent with several authors [37] [38] [39] included who demonstrated that sensitivity analysis has a significant impact on assessing the effects of applying a certain action throughout a process. As a result, its use is critical in the decision-making process.…”
Section: Presentation Of Results and Discussionsupporting
confidence: 92%
“…The analysis demonstrated that the unit production cost is inversely proportional to profit while the selling price per unit is directly proportional to profit. The results are consistent with several authors [37] [38] [39] included who demonstrated that sensitivity analysis has a significant impact on assessing the effects of applying a certain action throughout a process. As a result, its use is critical in the decision-making process.…”
Section: Presentation Of Results and Discussionsupporting
confidence: 92%
“…Despite the generalizability of RMSs' definition, many authors, when referring to RMSs, limited their focus on specific systems. Indeed, RMSs' components are Computerized Numerically Controlled (CNC) machines, Reconfigurable Machines (RMs), Reconfigurable Machine Tools (RMTs), inspection machines, material-handling devices and systems (ElMaraghy, 2006;Bi et al, 2008b;Essafi, Delorme and Dolgui, 2012;Haddou Benderbal, Dahane and Benyoucef, 2017;Prasad and Jayswal, 2017;Borisovsky, Delorme and Dolgui, 2014;Vafadar, Hayward and Tolouei-Rad, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to identify all costs including the above items as well as any hidden elements related to the production of metal components for successful implementation. In addition, the development of a cost analysis model that estimates the production costs of a metal AM produced part versus a traditionally manufactured product is required, in such a model, using a sensitivity analysis to investigate various alternatives in the presence of uncertainty may lead to more robust results [176]. Impacts on supply chains, and the potential cost benefits of on demand production should also be factored into such models when assessing particular use cases [177].…”
Section: Metal Am Costsmentioning
confidence: 99%